Theoretical Basis for Talented Students of Higher Educational Institutions - Gulyamova Madina Yakubovna; Iroda Nodirovna Mahammatkulova; Rakhimov Nodir Mukhammadievich; Murodov Shahzod Tokhirjon oglu (Researchparks Publishing, 2021)
The aim of the work is to improve the content and organizational and pedagogical foundations of the technology of working with gifted students. Gifted students with certain general and specific abilities are distinguished by the following qualities: curiosity, search for answers to various questions, developed speech; rapid development of memory; early interest in science; a high level of cognitive activity and educational activity; purposefulness and originality in problem solving; development of thinking. As a result of the rapid development of informatization of education and the development of human capital, talent is not presented in the form of a triad: intellectual abilities, aspiration, creativity, but in the form of a sixtet - intellectual abilities aspiration, creativity, communication, autopsychological abilities, competence.